AI and Social Equity: Challenges and Opportunities in the Age of Automation - Loso Judijanto; Adam Mudinillah; Rashid Rahman; Nikhil Joshi (Yayasan Adra Karima Hubbi, 2025)
The rapid advancement of Artificial Intelligence (AI) and automation technologies has transformed various aspects of modern life, from labor markets to public services. While AI offers potential for innovation and efficiency, it also raises significant concerns regarding social equity, especially for marginalized and underrepresented communities. These concerns highlight the need for a critical examination of how AI systems may reinforce or mitigate existing societal disparities. This study aims to explore the challenges and opportunities that AI poses to social equity in the age of automation. The research focuses on identifying potential biases in AI-driven decision-making processes and assessing the impact of automation on employment, education, and access to services. Using a mixed-methods approach, the study combines qualitative interviews with stakeholders from policy, tech industry, and affected communities, alongside quantitative analysis of labor and demographic data. This methodological design allows for a comprehensive understanding of both structural and experiential dimensions of AI’s impact. The findings reveal that while AI has the potential to improve service delivery and expand access to information, its deployment often reflects and amplifies existing inequalities when ethical and inclusive frameworks are absent. Particularly in automated hiring systems and predictive policing, biases embedded in algorithms disproportionately affect vulnerable groups. The study concludes that addressing AI's social equity implications requires intentional design, inclusive policy, and sustained public engagement. As automation continues to reshape society, equity must become a central consideration in AI development and governance.